(untitled) (Journal of Nepal Geological Society, 2022)
This paper elaborates the rock slope deformation analysis in a complex rock mass i.e., metamorphic rocks. At the powerhouse of the Middle Bhotekoshi Hydroelectric Project, Sindhupalchok, Nepal, the rock slope deformation has occurred as a result of excavation of natural rock slope turning into the cut-slope. The deformation yielded by different causes were studied and analyzed by kinematic analysis, inclinometer data combining with numerical modeling. For the study and analysis of the cut-slope, geotechnical data were collected from the existing rock types of the cut-slope. At first, the kinematic analysis was carried out by using the stereonet plot in DIPS. The core logs of investigation time were reviewed and tried to prepare the geological model of this part. The finite element method was used to analyze the stability of the rock cut-slope based on the geotechnical data. Similarly, the inclinometer recorded data were used to compare with the analyzed deformation data and tried to find out the weak zone within the cut-slope. The kinematic analysis showed that the rock slope has the least probability of failure. The result showed that there was tolerable deformation on the slope based on inclinometer data but failure was observed at PSIN-1 where the weak zone is present. The deformation at PSIN-1 was found to be in the thin ductile deformed zones where rock characteristics were different which was considered not operative for the slope stability.